Eriobotrya balgooyi - Tanggaraju, S.; Felix, E. C.; Damit, A.; Khoo, E.; Matusin, Dg Ku Rozianah, M.; Colin Ruzelion Maycock; Mohd Yusof, Nur Adillah, M.Y.; Nilus, R.; Sugau, J.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Eriobotrya balgooyi is a small tree recorded from Mount Kinabalu and Mount Tumbuyukon in Kinabalu Park. To date, the estimated area of occupancy (AOO) and extent area of occupancy (EOO) are both 8 km2 respectively. It is found in ligneous scrub with ultramafic soils with an altitude range between 2,420–2,560m, therefore the most plausible threat that could affect the population would be climate change. The impact of climate change on the one site of the species could cause it to become Critically Endangered in a short window of time. Hence, it is assessed as Vulnerable. Eriobotrya balgooyi is endemic to Sabah, Malaysia. It is restricted to Mount Kinabalu and Mount Tumbuyukon located in Kinabalu Park.